PELUANG REVITALISASI KOPERASI NELAYAN (STUDI KASUS KOPERASI NELAYAN KOTA BENGKULU) - Ratu Eva Febriani; Barika Barika (Universitas Negeri Padang, 2014)
Fishing cooperatives is an institution that can serve as a forum to improve the welfare of fishing communities . The aim of this study is to assess the fishing cooperative revitalization opportunities. Primary data is used to outlining the problems of this study with sample of 50 people and using SWOT analysis. The discussion is limited to lifting cases in Kopnel Bengkulu city. The results showed that the institutional of Kopnel Bengkulu City is weak , but have considerable opportunities to develop, so it is good to do revitalization . Keywords: Fishing cooperatives, revitalization, SWOT, Bengkulu City.